Pengaruh Penggunaan Media Pembelajaran Powtoon terhadap Motivasi dan Hasil Belajar Materi IPS pada Siswa Kelas IV Sekolah Dasar Kecamatan Cluwak Kabupaten Pati - Dewi Yuliati; Santoso Santoso; Gunawan Setiadi (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine the effect of social studies learning motivation with powtoon learning media on class IV students, determine the effect of social studies learning outcomes with powtoon learning media on fourth grade students, find out the difference in the influence of social studies learning motivation with powtoon learning media on fourth grade students. . This study uses an experimental approach with a pure experimental type because of the experimental and control classes, while the design used is the pretest posttest control group design. The data collection technique used a test consisting of pretest and posttest, and also used a questionnaire on learning motivation. The instrument test consists of a validity test, a reliability test, a difficulty level test for items, and a question item difference test. Data analysis used normality test and homogeneity test. Hypothesis test using N-gain and t test in regression analysis. In this study, Powtoon learning media affects the social studies learning motivation of fourth grade students at SDN Ngablak 01, this is based on the acquisition of the average (mean) N-Gain score on the motivational measurement scale in the experimental class by applying the Powtoon learning media to obtain a value of 57% included in quite effective category. (2) Powtoon learning media has an effect on social studies learning outcomes for fourth grade students at SDN Ngawen. this is based on the acquisition of the value that the average (mean) N-Gain score of the learning outcome measurement scale in the experimental class by applying the Powtoon learning media obtains a value of 55% which is included in the quite effective category. (3) Based on the results of the independent sample test table test results, it is known that the sig value on Lavene's Test is 0.548> 0.05 which this result has the N-Gain t test result, the score is greater than the learning outcome 0.541> 0.05. It can be concluded that learning motivation has a greater impact than learning outcomes using powtoon media in grade IV SD social studies material in Cluwak District, Pati Regency.